For Rigour in Organizational Management Theory Research. (21st August 2012) - Donaldson, Lex; Qiu, Jane; Luo, Ben Nanfeng
abstract Rigour is required in examining the empirical validity of theories in organizational management, and is often considered to be the opposite of creativity in the development of knowledge about managing organizations. In this article, we argue that rigour is necessary in the enterprise of organizational management research. Moreover, it can actually be a contributor to creativity. The issue is not rigour versus creativity, but rather how rigour can foster creativity. We show that rigour in both theory and methodology can foster creativity. Rigour in theory provides the logical thinking that is the foundation that allows the development of sound theory. This can be achieved in various ways, including theory building, mathematical modelling, causal modelling, and theory analysis. Rigour in methodology can assist creativity in quantitative integration. The contribution of rigour to creativity is evidenced by the recently created statistico‐organizational theory and other new advancements in the field of structural contingency research.